A Study of Wear Articular Cartilage of Synovial Human Knee Joint Using Non-Newtonian Elastic Mathematical Model - Abdullah, Enas Yahya; Khdhie, Hala (Iraqi Journal of Science, 2020)
In this paper, the wear in layers of articular cartilage was calculated, parameters effective on elastic deformation were studied in normal and diseased knee joints, and relations between elastic deformation and squeeze film characteristics under lubrication condition were discussed with using a mathematical model. Conferring to the results obtained, elastic deformation effects on the performance of synovial human knee joint were analyzed from medical and dynamics perspectives. Relationships between elastic deformation and wear of layers were also discussed.